Bài 1:
x3+y3=152=> (x+y)(x2-xy+y2)=152
Mà x2-xy+y2=19
=> 19(x+y)=152=> x+y=8
Ta cũng có x-y=2
=> x=5;y=3
Bài 2:
x2+4y2+z2=2x+12y-4z-14
=> x2+4y2+z2-2x-12y+4z+14=0
=> (x2-2x+1)+(4y2-12y+9)+(z2+4z+4)=0
=> (x+1)2+(2y-3)2+(z+2)2=0
=> (x+1)2=(2y-3)2=(z+2)2=0
=> x=-1;y=3/2;z=-2
Bài 3\(\left(\frac{1}{x^2+x}-\frac{1}{x+1}\right):\frac{1-2x+x^2}{2014x}=\left(\frac{1}{x\left(x+1\right)}-\frac{1}{x+1}\right):\frac{\left(1-x\right)^2}{2014x}=\frac{1-x}{x\left(x+1\right)}.\frac{2014x}{\left(1-x\right)^2}=\frac{2014}{\left(x+1\right)\left(1-x\right)}=\frac{2014}{1-x^2}\)